Older Adults Vs Middle-Aged Adults: Walking Velocity (International Journal of Innovative Research in Computer Science & Technology, 2020)
The objective of the present study was to  evaluate walking velocity of middle-age adults and older  adults. Ten adults (5 middle age adults and 5 older adults)  were recruited from a local community. They were all  physically healthy and not injured in the last 6 months.  Their whole body landmark position data were collected  during subsequent 5-minute walking on a straight track  (15m long). The results indicated that walking velocity of  middle-age adults were faster than that of older adults  during their natural gait. The study concluded that  middle-age adults’ likelihood of falls may be higher than  older adults’ likelihood of falls.
Keywords: WV; Middle age; Older; Foot force